(untitled) (Серія: Історія. Політологія, 2021)
В статті проаналізовано джерельний потенціал матеріалів таборової «живої» газети «Промінь», яка з моменту свого заснування стала справжнім літописцем табору, бо опубліковані на її шпальтах матеріали містили значний обсяг інформації про життя та повсякдення інтернованих вояків-українців у Стшалкові. Здебільшого такі матеріали розміщувались у рубриці «Таборове життя», і їх вивчення дозволяє отримати цінний фактаж про особливості побуту таборян, їх основні заняття та дозвілля. Разом з тим в газеті публікувались критичні статті, які торкались багатьох гострих проблем перебування інтернованих частин Армії УНР у таборі Стшалково. Протягом усього часу свого видання газета справляла потужний вплив на процес формування світогляду таборян, заохочуючи їх до участі у збірках коштів на різні значущі громадсько-соціальні потреби. Така позиція редколегії часопису забезпечила йому моральну підтримку з боку більшості інтернованого вояцтва, для якого вихід кожного числа газети ставав подією у невеселому таборовому житті. Попри всі труднощі таборової ізоляції, редколегія знаходила можливості для отримання новинної і суспільно значущої інформації та її уміщення на сторінках «Променя», послідовно обстоюючи при цьому національно-державницькі ідеали УНР. The article analyzes the source potential of the materials of the camp «living» newspaper «Ray», which was issued by interned Ukrainian soldiers first in the Lancut camp (Poland), and from the very beginning of its withdrawal it won the favour of the vast majority of the campers. After their relocation to Strzalkovo, the magazine continued its life in the old format – when the editorial board prepared 2-3 copies of «Ray» (typing them), after which his materials were distributed weekly in the camp by saying them to the generally interned from the stage of the camp theatre. Thanks to this practice, the magazine has become an integral part, and campers have been looking forward to its next issues – to hear a lively and sharp Ukrainian word, which branded various negative aspects of the camp’s everyday life. At the same time, its editors faced many difficulties in preparing almost every issue of the magazine, which were due to the banning of some of its materials by censorship, and the reluctance of individual campers to become the target of sharp satirical notes. At the same time, the command of a group of interned troops understood the usefulness of such a publication to maintain the morale of the military. The camp newspaper «Ray» became a real chronicler of the camp, because the materials published in its columns contained a significant amount of information about the life and everyday life of interned Ukrainian soldiers in Strzalkovo. Most of these materials were placed in the section «Camp life», and their study allows you to get valuable facts about the peculiarities of the life of campers, their main occupations and leisure. At the same time, the newspaper published critical articles that touched on many acute issues, including on the unwillingness of some officers of the Army Ukrainian People’s Republic to use the Ukrainian language at work and in everyday communication, official and extra-official relations of officers and Cossacks, unworthy behaviour of certain employees of the camp commandant’s office. Throughout its publication, the newspaper has had a powerful influence on the process of forming the worldview of campers, encouraging them to participate in fundraising for various important social needs. This position of the editorial board of the magazine provided him with moral support from the majority of the interned army, for which the publication of each issue of the newspaper became an event in the gloomy camp life. Despite all the difficulties of camp isolation, the editorial board found opportunities to obtain news and socially significant information and publish it on the pages of «Ray». By publishing materials about the sanctity and invincibility of the Ukrainian liberation struggle, the newspaper always stood in defence of the national-state ideals of the Ukrainian People’s Republic.